The variations of very-high energy γ-quanta flux from the blazar 3C 66A in 2002 - Fidelis, V.V. (Кинематика и физика небесных тел, 2005)
The extra-galactic source blazar 3C 66A was observed in 2002 with the aid of the air Cherenkov telescope GT-48 dedicated for stereoscopic measurements of extensive air showers (EAS). The analysis of the observational data obtained during the period November–December with a total exposure time of 6h40m revealed a γ-ray flux atE >1 TeV ≈ 93% of the steady flux from the Crab Nebula at 5.03 σ level. The observations have shown variations of flux intensity from source in the very-high energy (VHE) band which may be interpreted as low and high states of the object during the observing period. The temporal properties of object are correlated well with quasi-simultaneous observations in the 2–10 keV energy band as measured by the All Sky Monitor onboard RXTE.